Optimizing Treatment Outcomes in Crohn's Disease: A Comprehensive Systematic Review and Meta-Analysis of Regenerative Therapies with Emphasis on Platelet-Rich Plasma - Marcia Carolina Mazzaro; Ana Emília Carvalho de Paula; Livia Bitencourt Pascoal; Livia Moreira Genaro; Isabela Machado Pereira; Bruno Lima Rodrigues; Priscilla de Sene Portel Oliveira; Raquel Franco Leal (MDPI AG, 2024)
Background/Objectives: Crohn's disease (CD) is a chronic inflammatory disorder that significantly affects patients' quality of life; conventional treatments often provide limited relief. Methods: This systematic review and meta-analysis explored the potential of regenerative therapies, particularly platelet-rich plasma (PRP), as an adjunctive treatment for CD. The study protocol was registered with PROSPERO (CRD42024576683), and a comprehensive search was conducted across major databases, such as PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials. The search included terms related to CD and PRP. Studies assessing the efficacy of PRP in CD treatment were selected. Statistical analysis was conducted using the PICO framework with R software (version 4.3.2) and meta-package. Results: Of the 29 studies identified, 10 met the inclusion criteria, comprising pilot studies and controlled trials. Nine studies focused on Crohn's disease perianal fistulas (CDPF), and one focused on colonic CD. Among 138 patients with CDPF, 82.44% showed some fistula healing after PRP treatment, with 48.05% achieving complete resolution. In a sub-analysis, combining PRP with a stromal vascular fraction (SVF) resulted in a 58.62% complete healing rate, whereas combining PRP with adipose-derived stem cells (ASCs) showed even higher efficacy at 85.89%. PRP treatment alone resulted in a lower complete healing rate of 38.51%. PRP was well tolerated, with minor side effects such as localized pain. Conclusions: These findings suggest that PRP, especially when combined with stem cells, offers a promising new approach for treating CD. However, larger trials are needed to confirm its long-term benefits and refine its clinical applications.